Impact of thermal conductivity on a horizontal absorbent isothermal wall in a porous medium with heat source and thermophoretic forces: Application of suction/blowing. Issue 8 (19th August 2022) - Hazarika, Silpi; Ahmed, Sahin
Abstract: The implanted porous media plays a key role in the performance of the fluid flow. To study the novelty of porous media in a two‐dimensional fluid motion associated with thermophoretic forces, viscous dissipative heat, and variable thermal conductivity over a permeable horizontal surface, we have adopted appropriate similarity transformation to convert the prominent partial differential equations to nonlinear ordinary differential equations in nondimensional form. MATLAB Bvp4c code is employed for the conservation of equations with the appropriate converted boundary conditions and this finite difference scheme is found stable. Furthermore, we have performed a comparison test for validity and accuracy test and established a satisfactory agreement with former literature. The effect of porosity and thermal conductivity in presence of suction/blowing over the fluid velocity and temperature are significant. In this study, the fluid velocity is enhanced for heat generation and thermal conductivity in presence of blowing. The importance of porous media and such study can be experienced in various branches like petroleum engineering, hydrogeology, biophysics, material science, and so forth.